Assembly of Copper Phthalocyanine on TiO2 Nanorod Arrays as Co-catalyst for Enhanced Photoelectrochemical Water Splitting - Li, Yuangang; Yang, Mengru; Tian, Zimin; Luo, Ningdan; Li, Yan; Zhang, Haohao; Zhou, Anning; Xiong, Shanxin (Frontiers in Chemistry, 2019)
A photoelectrochemical device was achieved by interfacial self-assembly of macrocyclic π-conjugated copper phthalocyanine (CuPc) on surface of TiO2 nanorod arrays (NRs). The photocurrent density of the elegant TiO2@CuPc NRs photoanode reaches 2.40 mA/cm2 at 1.23 V vs. RHE under the illumination of 100 mW/cm2 from AM 1.5G sun simulator, which is 2.4 times higher than that of the pure TiO2. At the same time, the photoelectrochemical device constructed through this strategy has good stability and the photocurrent density remain almost no decline after 8 hours of continuous operation. The Mott-Schottky and LSV curves demonstrate that CuPc act as a co-catalyst for water oxidation and a possible mechanism is proposed for water oxidation based on careful analysis of the detailed results. The holes from VB of TiO2 photogenerated by electrons exciting are consumed by a process in which Cu2+ is oxidized to Cu3+ and Cu4+, and then oxidize water to produce oxygen. CuPc species is considered to be a fast redox mediator to reduce the activation energy of water oxidation in and effectively promote charge separation.